Creation and ecological trail of the precocious spring wheat forms, obtained by the use of cell technology (Experimental biology, 2016)
398 R0 plants were regenerated from long-term cultivated calli of 28 commercially important new generation’s wheat varieties. From these 110 plants of 18 varieties brought up R1 seed generation. 47 lines (37%) from those 110 lines of R1 we selected that had accelerated term of maturation on 3-6 days compared to initial varieties. Ecological trial of selected lines in R2 generation at North and Central Kazakhstan conditions allowed to prove the expression of the precocity trait (accelerated development on 1-8 days) and to select the precocious forms (25-47,7% from the number of lines tested) with high productivity and drought resistance traits which were most prospective for each region. Thus, we have shown the principal possibility of the creation of spring wheat precocious forms with the complex of valuable economic-biological traits for growing in North and Central Kazakhstan by the use of cell technology developed by us.
Keywords: wheat; callus tissues; regenerated plants; precocity; ecological trial.